Trigona Jurine, 1807 Bees (Hymenoptera: Apidae) as Pests of Physic Nut (Euphorbiaceae: Jatropha curcas) in Peru - Rasmussen, Claus (2009)
Trigona amalthea and T. truculenta collect plant fibers by stripping pieces of bark (average size 3x11 mm) of branches and twigs of the physic nut in San Martín, Peru. They also, as does T. fuscipennis, chew and destroy the ribs in the palmate-veined leaves and the petiole. From the leaves they were observed to gather both plant fibers and resins. Most of the Trigona species damaging crops belong to a monophyletic group of bees that builds exposed nests, thus requiring both fibers and resin for construction and maintenance of their colony. The control of the damage is best achieved by locating and removing the nest.